Implementation of The Legal Obligation to Complete Inpatient Medical Records for Cancer Patients at Prof. Dr. I.G.N.G. Ngoerah Denpasar General Hospital - Gusti Ayu Eka Sutrisnawati (Journal of Social Research, 2025)
The type of research uses the empirical legal research method quantitatively descriptive analytical, because it observes and examines reality in filling out the medical resume of inpatients at Prof. Dr.I.G.N.G.Ngoerah Denpasar Hospital. The approach used is factual, legislative, and conceptual approaches. This data comes from primary, secondary, and tertiary data along with primary, secondary, and tertiary legal materials. Data collection methods include observation, document studies, interviews and checklists. The results of this study show that: 1). Incompleteness in filling out inpatient electronic medical records at Prof. Dr. I. G. N. G. Ngoerah Denpasar Hospital has the potential to cause losses for patients and become the basis for a lawsuit. The lawsuit can be based on the non-conformity of electronic medical records with applicable legal standards and violations of patient rights, access to medical data by unauthorized parties, as well as non-compliance with regulations that can result in administrative and criminal sanctions for healthcare facilities, electronic medical resumes have legal implications because medical resumes are legal documents that can be used as evidence in medical dispute cases. Regulation of the Minister of Health Number 24 of 2022 regulates medical records, and incomplete filling can be considered a violation if there is negligence in filling it. The effectiveness of law enforcement in this case is influenced by the factors stated by Soerjono Soekanto, including clear regulations, competent law enforcement, adequate support facilities, public awareness, and a supportive work culture. 2). The factors causing the incompleteness of filling out inpatient electronic medical resumes are in the Gynecological Oncology Division (19%) and Surgical Oncology (18%). The factors causing the incompleteness of filling out an electronic medical resume are seen in terms of legal factors and non-legal factors.